2014
DOI: 10.1016/j.ijhydene.2013.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostics of PEM fuel cell in a particle filtering framework

Abstract: Proton Exchange Membrane Fuel Cells (PEMFC) suffer from a limited lifespan, which impedes their uses at a large scale. From this point of view, prognostics appears to be a promising activity since the estimation of the Remaining Useful Life (RUL) before a failure occurs allows deciding from mitigation actions at the right time when needed. Prognostics is however not a trivial task: 1) underlying degradation mechanisms cannot be easily measured and modeled, 2) health prediction must be performed with a long eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(99 citation statements)
references
References 32 publications
1
98
0
Order By: Relevance
“…Data-driven approaches are more widely used for fuel cell diagnostics, that is, extracting the features by applying signal processing techniques to the sensor data, and discriminating fuel cell faults with extracted features [9][10][11][12][13]. Compared to fuel cell diagnostics, fewer studies have been devoted to fuel cell prognostics, and among these studies, training data from a fuel cell system is required to generate the input-output relationship of the fuel cell model for the prediction of future performance [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven approaches are more widely used for fuel cell diagnostics, that is, extracting the features by applying signal processing techniques to the sensor data, and discriminating fuel cell faults with extracted features [9][10][11][12][13]. Compared to fuel cell diagnostics, fewer studies have been devoted to fuel cell prognostics, and among these studies, training data from a fuel cell system is required to generate the input-output relationship of the fuel cell model for the prediction of future performance [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, hybrid approaches can be used that operate with two kinds of information (the degradation model and measurement data). According to bibliographic studies, particle filter is a hybrid method that meets our requirements and has shown its capability in multiple applications [56,57]. The degradation model that we aim to use in future work is that of output power, as mentioned in [58].…”
Section: Future Work: Improving the Resultsmentioning
confidence: 99%
“…The black box modeling has already been investigated [21,31]. The physical based approach is developed with this first step of modeling.…”
Section: Phm Of Fuel Cellmentioning
confidence: 99%